The Implementation of Outing Class in Project Based Learning at TK ABA Jember - Misyana; Tri Endang Jatmikowati; Ifrohatul Husnah (Universitas Panca Sakti Bekasi, 2023)
Outing class also considered as learning activity outside the classroom or field trip that are one of the series or stages in project-based learning. The purpose of the research is to know how the implementation of outing class on project-based learning. The research was conducted in TK ABA in Jember regency that has implemented project-based learning based on local content. The research method used is qualitative. The aim of this research is to describe the implementation of outing class in project-based learning. To strengthen the result of the research was done by data triangulation through observation, interview and documentation. The object of this research are early child around 5 to 6 years old which are involved in outing class activity on project-based learning. The result of this research shows that outing class activity in project-based learning create the learning atmosphere more challenging and enjoyable since the children can interact with other people beside their teacher so that it can affect their critical thinking ability. collaboration, communication and creativity improved related to the expectations during the process in project activity. Keywords: Outing Class, Project Based Learning